Coping strategies, stress, physical activity and sleep in patients with unexplained chest pain - Kjellgren Karin I; Gaston-Johansson Fannie; Jerlock Margaretha; Welin Catharina (BMC, 2006)
Abstract Background The number of patients suffering from unexplained chest pain (UCP) is increasing. Intervention programmes are needed to reduce the chest pain and suffering experienced by these patients and effective preventive strategies are also required to reduce the incidence of these symptoms. The aim of this study was to describe general coping strategies in patients with UCP and examine the relationships between coping strategies, negative life events, sleep problems, physical activity, stress and chest pain intensity. Method The sample consisted of 179 patients younger than 70 years of age, who were evaluated for chest pain at the emergency department daytime Monday through Friday and judged by a physician to have no organic cause for their chest pain. The study had a cross-sectional design. Results Emotive coping was related to chest pain intensity (r = 0.17, p = 0.02). Women used emotive coping to a greater extent than did men (p = 0.05). In the multivariate analysis was shown that physical activity decreased emotive coping (OR 0.13, p < 0.0001) while sex, age, sleep, mental strain at work and negative life events increased emotive coping. Twenty-seven percent of the patients had sleep problems 8 to14 nights per month or more. Permanent stress at work during the last year was reported by 18% of the patients and stress at home by 7%. Thirty-five percent of the patients were worried often or almost all the time about being rushed at work and 23% were worried about being unable to keep up with their workload. Concerning total life events, 20% reported that a close relative had had a serious illness and 27% had reasons to be worried about a close relative. Conclusion Our results indicated that patients with more intense UCP more often apply emotive coping in dealing with their pain. Given that emotive coping was also found to be related to disturbed sleep, negative life events, mental strain at work and physical activity, it may be of value to help these patients to both verbalise their emotions and to become cognizant of the influence of such factors on their pain experience.